Analysis and Fate of Toxic Glycoalkaloids from Solanum tuberosum in the Terrestrial Environment - Jensen, P.H. (University of Copenhagen, 2008)
Many plants and microorganisms produce toxins and there has been an increased interest in the fate of natural toxins in the terrestrial environment within the last decade. Several natural toxins have been detected in the soil or in surface, drainage, or soil water. The presence of natural toxins in the terrestrial environment is of concern, because they may have unintended effects on various organisms or because they may contaminate valuable drinking water resources. One of the most important crops in the world, the potato plant, produces the two toxic glycoalkaloids, α-chaconine and α-solanine. These compounds are present in all parts of the potato plant, and previous studies indicate that they may be relatively persistent in the terrestrial environment. Potato plants are often grown on sandy soils under heavy irrigation; both conditions increase the risk of leaching. Hence, the potato glycoalkaloids could possible be a risk in the terrestrial environment. The aim of the Ph.D. work presented here was to investigate the fate of the potato glycoalkaloids, αchaconine and α-solanine, in the soil and groundwater environment. As a part of the project, a sensitive and specific analysis method using liquid chromatography-electrospray ionization time-offlight mass spectrometry (LC-ESI-MS-TOF) was developed in order to be able to detect the glycoalkaloids in environmental samples. The fate of the two glycoalkaloids in the environment was investigated in both laboratory and field studies. In the laboratory, degradation of the glycoalkaloids was studied in soil and groundwater; the latter enabled identification of formed degradation products. A conventional potato field was used in a field study, where the glycoalkaloid content was followed in plants, soil, and groundwater during one year. The present Ph.D. thesis consists of an introductory section and four manuscripts. One of the manuscripts is already published. The introduction section consists of three major parts. The first part is a literature review of potato glycoalkaloids in general, with focus on the aspects relevant for their environmental fate. The second part comprises the analytical work. A review of the many methods, which are or have been used for determination of the glycoalkaloids, is given. Further, the analytical methods used in the present work are discussed in detail. The fate of the potato glycoalkaloids in the environment is discussed in the last part, and this section is primarily based on the results obtained in the present work. The fate studies are related to similar fate studies of other natural compounds. Manuscript I describes the development of a sensitive LC-TOF-MS method for determination of the two potato glycoalkaloids and their common aglycone, solanidine, in environmental samples. The development included optimization of a new HPLC method and optimization of the response by the TOF-MS. Additionally, the fragmentation patterns of the compounds were presented. The performance of the method was evaluated with respect to linearity, precision, and detection limits. The obtained detection limits were in the range 2.2-4.7 µg/L. The work showed the LC-TOF-MS to be a powerful tool for quantitative studies of glycoalkaloids including identification of unknown metabolites. Manuscript II is a lab degradation study of α-chaconine and α-solanine in groundwater sampled from the field location at Fladerne Bæk, Denmark. The degradation of the glycoalkaloids and the formation of metabolites were followed by LC-MS. The degradation was shown to be primarily microbial and proceeded as a cleavage of the three carbohydrate units. The metabolites, β1-solanine, γ-solanine, and solanidine were formed from α-solanine, while β-chaconine, γ-chaconine, and solanidine were detected from α-chaconine. This is the first report of the formation of β1-solanine by microbial degradation. The metabolite, solanidine, was also degraded, but no further metabolites could be detected. Thus, this study shows that indigenous groundwater microorganisms are capable of degrading the glycoalkaloids. Manuscript III is a comprehensive field study. The glycoalkaloid content in potato plants, soil, and groundwater from a potato field was followed during a growth season and the following winter. The field location was a sandy soil from Fladerne Bæk, Denmark used for potato growing. In the plants, the maximum glycoalkaloid concentration of 22 g/kg dry weight was found in June. The total plant amount of glycoalkaloids was at maximum in July (25 kg/ha), after which it decreased during plant senescence to below 0.63 kg/ha in October. In the upper soil, glycoalkaloids were found in concentrations of up to 2.8 mg/kg dry weight. The highest soil load was estimated to be 0.6 kg/ha in September. Glycoalkaloids were still present in the soil in March, despite no further transfer from the plants during winter. Hence, the dissipation in the soil was slow during winter. The amount of glycoalkaloids found in the soil accounted for only a minor fraction of the amount present in the plants. The investigation also showed degradation of the glycoalkaloids in the potato plant during decay. Thus, the major dissipation route for the glycoalkaloids was proposed to be degradation within the plant material. No traces of glycoalkaloids were detected in the groundwater sampled from 2-4 m below the potato field during the growth season. From these results, the leaching potential of the glycoalkaloids is evaluated to be low. In Manuscript IV, the degradation of the potato glycoalkaloid, α-solanine, was followed in three agricultural soils, including soil from Fladerne Bæk. Similar degradation pattern was found in all soils, where a fast initial degradation was followed by a slower phase. The pattern was well described by a sum of two first-order expressions. Half-lives ranging from 1.8-4.1 days were found for the three topsoils at 15 ºC, but residuals were still detected by the end of the experiment after 42 days. For the Fladerne Bæk soil, the degradation was additionally followed at 5 ºC in both top- and subsoil and here half-lives of similar lengths ranging from 4.7-8.7 days were found. Overall, fast degradation was found in both top- and subsoil even at low temperatures, and from these results, the risk of glycoalkaloid leaching to the groundwater appears to be limited.